Objectively Measured Physical Activity Increases Only in Males During a Summer Camp for Obese Children - Izzicupo, Pascal; Di Blasio, Andrea; Di Credico, Andrea; Ghinassi, Barbara; Capranica, Laura; Napolitano, Giorgio; Di Baldassarre, Angela; Modestini, Elisabetta; Di Pietro, Mario (Frontiers in Sports and Active Living, 2021)
Childhood obesity is a major public health challenge. Summer camps for children with obesity represent an alternative setting to improve eating and physical activity habits. Here we evaluated if the participation in the camp improves objectively measured physical activity and sedentary behavior and whether there are differences between male and female participants. Twenty-eight children, 13 males and 15 females (BMI > 97°, weight excess > 30%, Tanner stage I) agreed to participate in an eight-day camp. During the summer camp, children participated in sports-like games and outdoor activities for at least three hours a day, and the school-camp staff also provided a theoretical nutritional learning plan. Accelerometry-derived physical activity was measured through the Sensewear Mini Armband during a week at home and during the camp experience. Before camping, the participants were far above the minimum daily values of moderate to vigorous-intensity physical activity (MVPA) to be considered sufficiently active (≥ 60 min/day), but male participants were more active than females (MVPA: 186.2 ± 94.2, 111.0 ± 64.7, P = 0.020). Male participants increased their MVPA (234.3 ± 114.8, P = 0.020) while females not (111.9 ± 52.9, P = 0.020). No difference emerged for the sedentary behavior neither before nor during the camp. This study suggests that participation in a summer camp for obese children can determine different responses in physical activity levels, depending on the sex of young participants. Thus, summer camps for obese children should put particular attention on female participants, besides reducing sedentary behavior in both males and females.